MN-CR ISOTOPE SYSTEMATICS OF THE D'ORBIGNY ANGRITE - Glavin D.P.; Kubny A.; Jagoutz E.; Lugmair G.W. (My University, 2004)
We have conducted a detailed study of the Mn-Cr systematics of the angrite D'Orbigny. Here, we report Cr isotopic abundances and Mn/Cr ratios in olivine, pyroxene, glass, chromite, and bulk rock samples from D'Orbigny. 53Cr excesses in these samples correlate well with their respective Mn/Cr ratios and define an isochron with a slope that corresponds to an initial 53Mn/55Mn ratio = (3.24 ± 0.04) - 10-6 and initial 53Cr/52Cr ratio of e(53) = 0.30 ± 0.03 at the time of isotopic closure. The 53Mn/55Mn ratio of the D'Orbigny bulk rock is more than two-fold the 53Mn/55Mn ratio of the angrites Lewis Cliff 86010 (LEW) and Angra dos Reis (ADOR) and implies an older Mn-Cr age of 4562.9 ± 0.6 Ma for D'Orbigny relative to a Pb-Pb age of 4557.8 ± 0.5 Ma for LEW and ADOR. One of the most unusual aspects of D'Orbigny is the presence of glass, a phase that has not been identified in any of the other angrites. The Mn-Cr data for glass and a pyroxene fraction found in druses indicate that they formed contemporaneously with the main phases of the meteorite. Since the Mn-Cr age of D'Orbigny is ~5 Ma years older than the angrites LEW and ADOR, D'Orbigny likely represents an earlier stage in the evolution of the angrite parent body.